HYBRID WORK: EFFICIENCY OF DWI ELECTION SYSTEMS BASED ON E-VOTING AND CONVENTIONAL TO BOOST TRANSPARENCY IN 2024 ELECTIONS - Ibriza Sabrina; Sultan Sultan; Nurfadilla Nurfadilla; Kezia Patasik (Legislatif, 2023)
The dynamics of digitalization lead us to information disclosure and better work efficiency. The democratic party feels very close, 2024 will be the pinnacle of the democratic party along with developments in technology and information, in line with that digital participation will bring the 2024 Election into a more transparent realm. However, in reality, Indonesia is still stuck with network infrastructure problems and areas that are not evenly distributed. With a population and area that is so wide, leveling network infrastructure takes more time. The application of the electoral system in a conventional way is considered less effective in accommodating estimated vote recapitulation, so another system is needed to support the deficiencies in conventional elections. Writing this scientific paper aims to find out how the efforts in implementing hybrid working and achieving solutions with the enactment of the concept of hybrid working with the application of two systems based on e-voting and conventional. The type of research used is normative legal research with the Statute approach, Conceptual approach, and Comparative approach. The legal materials used are primary legal materials and secondary legal materials obtained from literature studies, the collected legal materials are then analyzed descriptively qualitatively. The results of this study indicate that the implementation of elections with one system, namely the conventional system, still has many problems in several aspects, especially the aspect of transparency, so the application of e-voting is present to complement the shortcomings of the conventional electoral system. Seeing that the regional structure and network infrastructure are not evenly distributed, based on the analysis results, applying the hybrid working concept in elections can balance the two systems with the hope that the 2024 election will become a more efficient, effective, and transparent democracy.